2018
DOI: 10.3386/w25036
|View full text |Cite
|
Sign up to set email alerts
|

When Studying and Nudging Don’t Go as Planned: Unsuccessful Attempts to Help Traditional and Online College Students

Abstract: Previously circulated as "Lack of Study Time is the Problem, but What is the Solution? Unsuccessful Attempts to Help Traditional and Online College Students." At the University of Toronto, we are indebted to the first-year economics instructors for their willingness to incorporate an experiment into their courses for a fourth consecutive year. We especially thank James Lahey, our web developer, for his tireless commitment to designing and perfecting the experiment's website, as well as for his help with organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Similarly, Schippers et al (2015) find that goal-setting significantly reduces inequalities in achievement if implemented early in students' academic careers. 24 However, our findings are consistent with recent experimental studies on goal-settings and nudges that also do not find any impact on test scores (see Dobriyoni et al (2017); Oreopoulos et al (2018); and Oreopoulos & Petronijevic (2019)). Similar to Oreopoulos et al (2018), we find that both treatments led to a significant change in students' time use behavior, but this positive change did not translate into improvements in academic outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, Schippers et al (2015) find that goal-setting significantly reduces inequalities in achievement if implemented early in students' academic careers. 24 However, our findings are consistent with recent experimental studies on goal-settings and nudges that also do not find any impact on test scores (see Dobriyoni et al (2017); Oreopoulos et al (2018); and Oreopoulos & Petronijevic (2019)). Similar to Oreopoulos et al (2018), we find that both treatments led to a significant change in students' time use behavior, but this positive change did not translate into improvements in academic outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…24 However, our findings are consistent with recent experimental studies on goal-settings and nudges that also do not find any impact on test scores (see Dobriyoni et al (2017); Oreopoulos et al (2018); and Oreopoulos & Petronijevic (2019)). Similar to Oreopoulos et al (2018), we find that both treatments led to a significant change in students' time use behavior, but this positive change did not translate into improvements in academic outcomes. An important difference is the the study by Oreopoulos et al (2018) was conducted in a developed country.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the study's sample size is very small and was selected from volunteers who responded to an advertisement-the students who might be most likely to enthusiastically make use of such an intervention-making it difficult to assess the external validity of these findings. Indeed, an attempt to replicate this online goal-setting exercise by one of this article's coauthors (Oreopoulos) found precise null effects for a sample of nearly 2,000 first-year university students, as well as for subgroups of students more at risk of poor academic performance (Oreopoulos, Patterson, et al 2018).…”
Section: Experimental Evidencementioning
confidence: 99%
“…This is certainly the case in developed countries like the United States, where it can be delivered online (see, for example, Gandhi et al, 2019; Paunesku et al, 2015; Yeager et al, 2016, 2019). The potential for deploying these interventions at a low cost is arguably even larger in higher education, where students already regularly interact with instructors online (Oreopoulos et al, 2017, 2018; Oreopoulos & Petronijevic, 2018).…”
Section: Methodsmentioning
confidence: 99%